The big five personality model and self-determined motivation in sport - Brinkman, C. S.; Weinberg, R. S.; Ward, R. M. (International Journal of Sport Psychology, 2016)
Using a sample of college athletes, we investigated the relationship between personality and self-determined motivation. Participants (N = 183) completed assessments of the Big Five model, using the Neuroticism Extraversion Openness- Five Factor Inventory-3 (NEO-FFI), and self-determined motivation to participate in sports, using the Behavioral Regulation in Sport Questionnaire (BRSQ). Structural equation modeling revealed that agreeableness, extraversion, and neuroticism were associated with greater self-determined motivation. Specifically, agreeableness was positively related to higher intrinsic motivation, and extraversion was positively related to autonomous extrinsic motivation. Additionally, neuroticism was positively associated with controlled extrinsic motivation and amotivation, and negatively associated with intrinsic motivation. Results are discussed in terms of personality research and possible applied implications, as well as methodological considerations.